Neraca Air Sungai Karang Anyar Sebagai Sumber Air Baku IPA Kampung Bugis - Rosmalia Handayani; Sutika Surya Indah Pertami; Aswar Amiruddin (Borneo Engineering : Jurnal Teknik Sipil, 2023)
IPA Kampung Bugis service area includes West Tarakan Sub-district and Central Tarakan Sub-district. These two sub-districts are the ones with the highest population density in the city of Tarakan, so in terms of water supply, it is necessary to carefully consider to avoid water deficits if there is no rainfall in Tarakan. This study aims to calculate the water balance of the Karang Anyar River as the raw water source for the IPA Kampung Bugis. The method used for availability calculations is the NRECA method. From the analysis of the reliable discharge Q90 of the Karang Anyar River using the NRECA method, an average Q90 reliable discharge of 55 liters/second is obtained, while based on the analysis of water needs in 2031, it is 295,852 liters/second. These results indicate that the Karang Anyar River is unable to meet the water needs in the IPA Kampung Bugis service area in the city of Tarakan